2010
DOI: 10.1007/s11240-010-9802-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of optimal and supra-optimal salinity stress on antioxidative defence, osmolytes and in vitro growth responses in Sesuvium portulacastrum L.

Abstract: The effect of optimal and supra-optimal concentrations (0, 200, 400 or 600 mM) of NaCl on the growth, osmotic adjustment and antioxidant enzyme defence was studied in the in vitro cultures of Sesuvium portulacastrum. A significant increase in growth, tissue water content (TWC) and fresh to dry weight ratio (FW/DW) was observed in the shoots exposed to 200 mM salt. Minimum damage to the membrane in terms of low relative electrolytic leakage (REL) and malondialdehyde (MDA) content and better osmotic adjustment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 45 publications
(58 reference statements)
7
55
0
1
Order By: Relevance
“…Generally known that APX has a higher affinity for H2O2 (μM range) than CAT and POX (mM range) and it may have a more crucial role in the management of ROS during stress (Gill and Tuteja, 2010;Karuppanapandian et al, 2011). Lokhande et al, (2011) observed that under NaCl-induced oxidative stress conditions, APX enzyme activities increased but CAT enzyme activities decreased in Sesuvium portulacastrum tissue cultures. Mohamed and Aly, (2004) reported that Fe-deficiency stress reduced activity of APX in Borage officinalis tissue culture.…”
Section: 42))mentioning
confidence: 90%
See 3 more Smart Citations
“…Generally known that APX has a higher affinity for H2O2 (μM range) than CAT and POX (mM range) and it may have a more crucial role in the management of ROS during stress (Gill and Tuteja, 2010;Karuppanapandian et al, 2011). Lokhande et al, (2011) observed that under NaCl-induced oxidative stress conditions, APX enzyme activities increased but CAT enzyme activities decreased in Sesuvium portulacastrum tissue cultures. Mohamed and Aly, (2004) reported that Fe-deficiency stress reduced activity of APX in Borage officinalis tissue culture.…”
Section: 42))mentioning
confidence: 90%
“…The Mn-SOD is resistant to both inhibitors; Cu/Zn-SOD is sensitive to both inhibitors whereas; Fe-SOD is resistant to KCN and sensitive to H2O2 (Ahmad et al, 2008;Gill and Tuteja, 2010;Karuppanapandian et al, 2011). There have been many reports of the increased activities of SOD under abiotic stresses induced with tissue culture techniques in a wide range of plant species, including heavy metals, such as Al, Cd, Cr, and Cu, hyperhydricity, salinity, gamma radiation, and drought (Gallego et al, 2002;Saher et al, 2004;Dewir et al, 2006;Israr et al, 2006;Erturk et al, 2007;Dasgupta et al, 2008;Sivritepe et al, 2008;Gupta and Prasad, 2010;Shehab et al, 2010;Yang et al, 2010;El-Beltagi et al, 2011;Helaly and El-Hosieny , 2011;Lokhande et al, 2011;Sen and Alikamanoglu, 2011;Xu et al, 2011;Patada et al, 2012) on the other hand, Fe-deficiency stress reduced activity of SOD (Lombardi et al, 2003). Advanced-antioxidant defense systems play an important role in plants not only to tolerate environmental stress but also to improve plants against these stresses.…”
Section: Antioxidant Defence Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the activities of major antioxidant enzymes such as SOD, APX, CAT and POX can be significantly increased in some halophytes. For example, in Sesuvium portulacastrum, 1 M NaCl treatment increased SOD, APX, CAT enzyme activities (Lokhande et al 2011). On the other hand, no significant change or a decrease in activity of some antioxidant enzymes were reported in Crithmum maritimum (Ben Hamed et al 2007).…”
Section: Introductionmentioning
confidence: 94%